PENERAPAN AUDIT MANAJEMEN ORGANISASI MANAJEMEN KEUANGAN DAN MANAJEMEN INVESTASI DI FEIN COLLECTION MENURUT PANDANGAN KRISTIANI - Nany, Magdalena; Alviya Rehatta, Marisa; Christy Anggeli Piri, Indah; Tjahjono, Pramadi; Widhi Rumekso, Ayub (Jurnal Pengabdian Bukit Pengharapan, 2024)
Good financial management is the key to success to achieve the company's goals and sustainability. So far, Fein Collection has never conducted a management audit of its financial function, the data collection techniques used are interviews and observations. Meanwhile, the analysis of management audit elements used identifies conditions, criteria, causes and consequences. Fein Collection should start developing documented financial management operating standards and procedures even though it is still a small business. Overall, although Fein Collection is a small business with a simple operational focus, the existence of formal programs and activity plans for financial management is still important. Although Fein Collection currently does not have any major investments, it is important for companies to start planning for future investments carefully.